Water-rock interaction during meteoric flushing of a limestone: implications for porosity development in karstified petroleum reservoirs - Smalley,PC; Bishop,PK; Dickson,JAD; Emery,D (Journal of Sedimentary Research A Sedimentary Petrology Processes, 1994)
The Lincolnshire Limestone, comprising a succession of Jurassic wackestones, packstones, and oolitic grainstones, forms an important carbonate aquifer in eastern England. Meteoric waters enter at outcrop and penetrate between confining strata at least 25 km down-dip. This water dissolves and interacts with the limestone, and even water samples collected at or near outcrop are calcite-saturated. Net limestone dissolution is thus a process that is most dominant in the near-surface environment. The Lincolnshire Limestone may be used as an analogue for karstified petroleum reservoirs, specifically those which have been buried and lost their unstable carbonate minerals (aragonite, high-Mg calcite) prior to uplift and karstification. -from Authors